(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. The article substantiates the necessity of using the possibilities of such a new component of public finance as public-private partnership finance for the reconstruction of the Ukrainian economy. Purpose. The purpose of the study is to determine the peculiarities of using the forms and types of public-private partnerships and their instruments in the implementation of partnership projects at all levels of government and by all its actors. Methods. The methodological basis of the study is the theoretical provisions of financial science, scientific works of well-known economists in the field of public-private partnership. To solve the research tasks, the paper uses the dialectical method of scientific knowledge to determine the content of public-private partnership finance and identify its instruments, conceptual and logical analysis and a systematic approach to the structure of this partnership, as well as the factor method, which allowed to identify and substantiate the determinants of public-private partnership development in Ukraine. Results. The research resulted in the identification of dialectical relations between different subjects of public-private partnership finance, the study of the unity of theory and practice in the implementation of the principles of public-private partnership and its instruments. It is substantiated that the fundamental characteristic of the methodology for cognizing the essence of public-private partnership finance and its instruments is the determinism of phenomena. Conclusions. The theoretical foundations for the use of financial instruments of public-private partnerships have been identified, which allows us to more clearly establish the methodological basis for their application in the context of the reconstruction of the Ukrainian economy, taking into account the experience of democratic countries. It is proved that public-private partnership finance can become a significant source of sustainable development investment in Ukraine in the context of war and reconstruction.